IMPLEMENTASI NILAI-NILAI PANCASILA DALAM PENDIDIKAN ANTI-KORUPSI UNTUK MENCEGAH KORUPSI SEJAK DINI - Arfiyansyah, Maruf; Sabrina, Azzahra Aulia; Hlaliyah, Nadiyatul; Aprilia, Mita; Aqila, Zakiya Nada; Hudi, Ilham (Komunitas Manajemen Kompetitif, 2024)
To stop corruption before it starts, anti-corruption education should incorporate Pancasila values. In order to instill the Pancasila ideals in the students of SMPN 40 Pekanbaru, Umri students perform community service. An anti-corruption socialization is held to carry out this activity, and topics covered include the definition, behaviors, consequences, illegal activities, and strategies for preventing corruption. Umri students were successful in helping SMPN 40 Pekanbaru students comprehend the risks and effects of corruption on society, as well as how to uphold morals and integrity, based on the educational socialization that has been conducted there.